Evaluation of myocardial function in pregnant women with speckle-tracking echocardiography - Arı, Selma; Ari, Hasan; Yılmaz, Mustafa; Bozat, Tahsin (The European Research Journal, 2020)
Objectives: The speckle-tracking technique calculates the regional rate, the strain and the strain rate from two-dimensional gray-scale visualizations. The aim of this study was to evaluate with speckle-tracking echocardiography the effects of the first, second and third trimesters of pregnancy on cardiac functions.Methods: One hundred five voluntary pregnant and 35 healthy women of reproductive age were included in the study. For echocardiographic evaluations, the 111 highest-quality visualizations were chosen: 24 cases in the first trimester, 31 cases in the second trimester, 32 cases in the third trimester and 24 healthy women as a control group. Global longitudinal, radial, and circumferential strain, and left ventricular (LV) rotation and twist were evaluated by two-dimensional speckle tracking echocardiography.Results: During pregnancy, the diameter, and volume of the left atrium, LV stroke volume, and the heart rate significantly increased beginning in the first trimester (p < 0.0125). The parameters of pulse-Doppler E velocity and tissue Doppler Em velocity significantly increased in the first trimester (p < 0.0125), whereas in the second and third trimester they decreased to control levels. Global longitudinal strain was significantly decreased in the third trimester of the pregnancy (p < 0.0125). Basal and apical LV rotation and twist were significantly increased in the third trimester of pregnancy (p < 0.0125). LV apical and basal reverse rotation rate were significantly increased in the first trimester of pregnancy (p < 0.0125).Conclusions: In the third trimester global longitudinal strain decreased whereas LV rotation and twist increased. Speckle-tracking echocardiography may be used to evaluate the effects of pregnancy and that provide further data on cardiac functions.